Analisis Lingkungan Eksternal Yang Terdapat Dalam PT. Unilever - Vikhri Septama Deni; Toni Ong; Vaness Kangnanda; Nico Fernando (Universitas 17 Agustus 1945, 2022)
The external environment is one aspect that becomes one of the handles of a company in identifying opportunities and threats that will be faced. This analysis was carried out with the aim of knowing what things could affect PT. Unilever on their part of the external environment. Qualitative data research method is the method used in collecting data for this study. From the results of this analysis, it will be explained how the external environment of the Unilever company is.